Combined Central Retinal Artery Occlusion and Presumed Ischemic Optic Neuropathy in Atrial Septal Defect: A Case Report - Thitiwichienlert, Suntaree; Kityarak , Kanitha; Wongkamchang, Nattapol; Buakhamsri, Adisai (Asian Medical Journal and Alternative Medicine, 2023)
A female presented with acute visual loss in the right eye. Fundus examination showed whitening retinal edema, disc swelling, and a cherry red spot in the right eye. Findings were suggestive of central retinal artery occlusion and ischemic optic neuropathy. Echocardiography revealed an atrial septal defect, which was successfully closed.